2010
DOI: 10.1210/en.2009-1385
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin-Induced Mitogenesis in the Subventricular Zone of the Maternal Brain during Early Pregnancy Is Essential for Normal Postpartum Behavioral Responses in the Mother

Abstract: High prolactin during pregnancy, which is essential for normal postpartum maternal behavior, increases neurogenesis in the subventricular zone of the lateral ventricle (SVZ) of the maternal brain. Because SVZ mitogenesis generates new olfactory neurons and may contribute to perception of novel odorants, we hypothesized that the prolactin-induced increase in SVZ mitogenesis during pregnancy might be important for normal maternal interactions with pups. To investigate this hypothesis, prolactin secretion was sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
179
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(199 citation statements)
references
References 65 publications
9
179
4
Order By: Relevance
“…Since multiple hormones change during pregnancy and lactation, Stat5 activation in bulge SCs could be due to Prl or another molecular factor. To test whether p-Stat5 activity is downstream from Prl signaling, we reduced systemic Prl levels with bromocriptine (BRC), a dopamine agonist that depletes secretion of pituitary Prl (Craven et al 2006;Larsen and Grattan 2010). We confirmed that treatment of mice with a low dose of BRC during pregnancy diminished serum Prl levels to nonpregnant levels while still permitting successful lactation (Fig.…”
Section: Prl Signaling Is Activated In Follicular Scs During Pregnancymentioning
confidence: 73%
See 1 more Smart Citation
“…Since multiple hormones change during pregnancy and lactation, Stat5 activation in bulge SCs could be due to Prl or another molecular factor. To test whether p-Stat5 activity is downstream from Prl signaling, we reduced systemic Prl levels with bromocriptine (BRC), a dopamine agonist that depletes secretion of pituitary Prl (Craven et al 2006;Larsen and Grattan 2010). We confirmed that treatment of mice with a low dose of BRC during pregnancy diminished serum Prl levels to nonpregnant levels while still permitting successful lactation (Fig.…”
Section: Prl Signaling Is Activated In Follicular Scs During Pregnancymentioning
confidence: 73%
“…For BRC experiments, 50 mg of 2-bromo-a-ergocryptine methanesulfonate salt (Sigma-Aldrich) was dissolved in a minimum amount of ethanol and brought up to 100 mL with sesame oil for each injection (Larsen and Grattan 2010). Starting the day after birth, females were injected subcutaneously with BRC or a VEH control.…”
Section: Brc Injectionsmentioning
confidence: 99%
“…For example, high levels of estradiol downregulate cell proliferation in the SVZ and consequently the number of adult-born neurons in the OB (Brock et al, 2010). Prolactin concentrations have been shown to be correlated with levels of proliferation in the SVZ and with the total number of adult-born neurons surviving in the OB (Shingo et al, 2003;Larsen and Grattan, 2010). Whether sensory environment, hormonal control or both regulate the structural changes we report here remains an open question.…”
Section: Regulation Of Integration Of Adult-born Neurons In Normal Anmentioning
confidence: 82%
“…More work is needed to follow up on this possibility while extending the analysis to possible steroidal modulation of cholinergic and/or serotoninergic inputs to the MOB. Other studies (Larsen and Grattan, 2010;Larsen et al, 2008) showed that chronic exposure to male pheromones over approximately 3 weeks (the duration of pregnancy) advanced the onset of maternal responsiveness in both virgin and pregnant female mice. This behavioral action of male pheromones was linked to the birth of new neurons in the ventricular zone followed by their migration along the rostral migratory stream into the MOB.…”
Section: Future Directionsmentioning
confidence: 97%